The Application of Project-Based Learning (PBL) in Teaching English for Specific Purposes (ESP) in Higher Education in Indonesia - Kultsum, Ummi; Defianty, Maya; Nadrah, Nadrah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractThis study aims to identify the impacts of applying project-based learning in English as Spesicic Purposes (ESP) classes in Islamic higher education. This research was held in the department of Family Law, Shariah and Law, State Islamic University Syarif Hidayatullah Jakarta. The study conducted a qualitative approach to explore students learning process. A semi-structured interview, class observation, and a test were used to collect the data of 40 student participants. The interpretation process and coding were conducted to analyse the data. The finding revealed ESP through PBL succeed to improve 87.5% of students in their English achievement. The PBL process also encouraged students in learning discipline and motivated them to solve the learning problems.AbstrakPenelitian ini bertujuan untuk mengidentifikasi dampak penerapan pembelajaran berbasis proyek di kelas English as Spesicic Purposes (ESP) di perguruan tinggi Islam. Penelitian ini dilaksanakan di Jurusan Hukum Keluarga, Syariah dan Hukum, Universitas Islam Negeri Syarif Hidayatullah Jakarta. Penelitian ini dilakukan dengan pendekatan kualitatif untuk mengeksplorasi proses belajar siswa. Wawancara semi terstruktur, observasi kelas, dan tes digunakan untuk mengumpulkan data dari 40 siswa peserta. Proses interpretasi dan pengkodean dilakukan untuk menganalisis data. Temuan tersebut mengungkapkan ESP melalui PBL berhasil meningkatkan 87,5% siswa dalam prestasi bahasa Inggris mereka. Proses PBL juga mendorong siswa dalam kedisiplinan belajar dan memotivasi mereka untuk memecahkan masalah pembelajaran.